P2.089 Antimicrobial Susceptibility Profile of Neisseria Gonorrhoeae Isolates in the Province of Québec: 2012. (13th July 2013) - Lefebvre, B; Labbé, A; Venne, S; Lambert, G; Fortin, C; Tremblay, C
Abstract : Background: Since 1988, the LSPQ (Laboratoire de santé publique du Québec) coordinates the Neisseria gonorrhoeae antimicrobial resistance programme, to support treatment guidelines updates. In the context of decreasing susceptibilities to 3 rd generation cephalosporins, azithromycin and cefixime were added to our antibiotic susceptibility panel. Methods: All N. gonorrhoeae strains isolated in clinical laboratories throughout the province were submitted to the LSPQ. The susceptibility profiles to azithromycin (AZI), cefixime (CEF), ceftriaxone (CFX), ciprofloxacin (CIP), ertapenem (ERT), gentamicin (GEN), penicillin (PEN), spectinomycin (SPE), tetracycline (TET), and tigecycline (TIG) were determined by the agar dilution method according to CLSI guidelines. WHO criteria were used to determine decreased susceptibility (DS) to cephalosporins. In 2010 and 2011, 5 antibiotics were tested (AZI, CEF, CFX, CIP and SPE) and 5 other antibiotics were added in 2012 (ERT, GEN, PEN, TET and TIG). Results: In 2012, a total of 502 strains isolated from 352 males (70%), 145 females (29%) and 5 unknown (1%) were tested. All strains were susceptible to cefixime, ceftriaxone and spectinomycin, 47.4% were resistant to ciprofloxacin, 35.7% to tetracycline, 26.3% to penicillin, and 1.4% to azithromycin (MIC = 16 mg/L). Gentamicin MICs ranged from 2 to 16 mg/L (MIC50 = 8 mg/L and MIC90 = 16 mg/L). Tigecycline MICs ranged from 0.03 to 2 mg/L (MIC50 = 0.5 mg/L and MIC90 = 1 mg/L). Ertapenem MICs ranged from ≤ 0.004 to 0.12 mg/L (MIC50 = 0.03 mg/L and MIC90 = 0.06 mg/L). DS to cefixime, DS to ceftriaxone and resistance to azithromycin data are presented in the attached table. Cefixime MIC of 0.125 mg/L was identified in 61 strains (6.6%) in 2010, 72 (9.0%) in 2011 and 20 (4.0%) in 2012. Conclusions: Although DS to cefixime has emerged in Québec, it remains at low level. Resistance to an alternative treatment option, azithromycin, is also emerging. This highlights the need to continue our resistance monitoring programme to support public health interventions.